An Investigation on Fibre Loading and Dimension towards Moisture Absorption in Biocomposites - Mohamad Amir, Muhamad Amirul Luttfi (IRC, 2016)
A series of environmentally friendly plasticized starch biocomposites were prepared using two types of plasticizers; conventional glycerol and choline chloride/urea (ChCl/Urea). The biocomposites were mixed with rice straw fibers to increase the mechanical properties of the biocomposites. Nevertheless, the use of reinforced fibers may interfere with moisture absorption causing the biocomposites to lose its strength. Thus the main focus of this study is to investigate the effect of fiber on moisture absorption mechanism of the biocomposites by varying its loading as well as dimension.